EKSISTENSI HUKUM ISLAM DALAM UNDANG-UNDANG RI NOMOR 36 TAHUN 2009 TENTANG KESEHATAN DI INDONESIA - Zul Anwar Ajim Harahap (Institut Agama Islam Negeri Padangsidimpuan, 2015)
This research begins from the reality of the existence of the provisions of the legislation Health which, according to the analysis of the authors has a dimension of Islamic law, so this research motivated the problem of the existence of Islamic law into national law and how Islamic law in the Law of health. The methodology was use a qualitative research, so that the analysis was use interpretative analysis, and comparative and inductive analysis. Results found is that Islamic law has existed in the legislation of health, seen from the passages that are similar to the context of Islamic law.